IMPROVING THE COMPETITIVENESS OF THE SMALL AND MEDIUM ENTERPRISES (SME) OF TROSO WEAVING CRAFT IN JEPARA REGENCY USING CAPITAL INTELLECTUAL ANALYSIS - Ngatindriatun, Ngatindriatun (Bina Nusantara University, 2018)
The aim of the research was to analyze the management of the SMEs of Troso Weaving Craft in Jepara Regency in relation to the human resources. In order that the SMEs can compete with today’s industry, the SMEs are required to be able to run their businesses professionally and to innovate, as well as to implement new breakthroughs. Therefore, the management of the SMEs needs to develop their intellectual ability and competitive advantage for their products. Intellectual capital is the intangible resource that can be used as the source of sustainable competitive advantage. The measurement of IC associated with competitive advantage was made against the elements of human capital, structural capital and costumer capital. Hence,this research discussed a model that relates the intellectual capital of the SMEs to the competitive advantage of the SMEs of Troso Weaving Craft in Jepara Regency. For the development of the model and hypothesis, the research used the Structural Equation Modelling (SEM), by taking the samples of 157 SMEs of Troso Weaving Craft selected in simple random sampling. The analysis results show that human capital, structural capital, and customer capital have the effect on competitive advantage. It means that the improvement of the competitive advantage for Troso Weaving Craft requires trainings in the managements of production, distribution, marketing and finance for all individuals and employees of the SMEs.